ROS production and removal of the herbicide metolachlor by air non-thermal plasma produced by DBD, DC− and DC+ discharges implemented within the same reactor. (13th June 2018) - Nani, Lorenzo; Tampieri, Francesco; Ceriani, Elisa; Marotta, Ester; Paradisi, Cristina
Abstract: There is a long-time interest in non-thermal plasma research applied to different environmental issues. We have recently developed a reactor for water treatment by air non-thermal plasma, which can be energized by either DC (positive or negative polarity) or AC high voltage. This paper reports and discusses the results of a study in which the performance of this reactor was tested under the three discharge regimes, DC−  and DC+  corona and DBD. Comparative experiments were carried out to characterize the system with regard to ROS (OH radicals, hydrogen peroxide and ozone) production and efficiency of treatment of the persistent herbicide metolachlor. DC−  discharges turned out to be significantly more effective in the production of ROS than either DC+  and DBD: higher ozone and hydrogen peroxide concentrations were obtained at any given energy input and OH radical formation was more efficient. Specifically, the rate of OH radical formation was (16.2  ±  1.2), (6.34  ±  0.11) and (4.15  ±  0.13) μ M kJ −1 for DC−, DBD and DC+, respectively. In view of these findings, it was not surprising that DC−  discharge regime sustained the most efficient process of metolachlor removal. The efficiency was evaluated considering the decay of metolachlor concentration as a function of time and of energy input, the G 50 parameter and the extent of mineralization achieved. The results clearly show that according to all these indicators DC−  discharges appear to be the best choice among the three which can be implemented in this reactor. HPLC/UV–Vis and HPLC/MSn analyses revealed that, regardless of the type of discharge employed, the same oxidation intermediates are formed from metolachlor, although at different rates depending on the discharge type. These observations therefore suggest that the same mechanisms and reactive species are probably involved in the degradation of metolachlor by DC−, DC+  and DBD air non-thermal plasma.